Plastibel Circumcision: Safest Technique in the Infants with the Experienced Hands: A Single Centre Experience - Rahman, Habib -Ur-; Iftikhar, Hina; Ali, Ghazanfar; Khoso, Mujahid Ali; Ahsan, Arooj; Ahmed, Naveed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the safety and efficacy of circumcision done by plastibel technique in infants up till six months of age. Study Design: Cross-sectional study. Place and Duration of Study: Department of Surgery, Combined Military Hospital, Multan, from Aug 2019 to Jul 2020 Methodology: The Department of surgery, Combined Military Hospital, Multan, from 2019 to 2020. A sample size of 140 patients was calculated via the EpiTools epidemiological calculator while keeping the significance level at 5% and a confidence level of 95%. Results: A total of 140 infants were circumcised with the plastibel technique. The age of the infants ranged from 21 days to six months with the mean age of 32.2 ± 10.5 days. Maximum circumcisions were done between 30-90 days of life. The best part of the circumcision was that no complication was observed during the study period. Conclusion: Plastibel circumcision can be done under local anaesthesia with the best possible safety in infants younger than six months of age.